Decreased Serum microRNA-21, microRNA-25, microRNA-146a, and microRNA-181a in Autoimmune Diabetes: Potential Biomarkers for Diagnosis and Possible Involvement in Pathogenesis - Yiwen Liu; Minglei Ma; Jie Yu; Fan Ping; Huabing Zhang; Wei Li; Lingling Xu; Yuxiu Li (International Journal of Endocrinology)
Objective. Previous studies have revealed dysregulated circulating microRNAs (miRNAs) in patients with type 1 diabetes (T1D). Here, we explored the serum levels of miR-21, miR-25, miR-146a, and miR-181a in patients with autoimmune diabetes (T1D and latent autoimmune diabetes of adults (LADA)) compared with type 2 diabetes (T2D) and nondiabetic individuals. Design, patients, and measurements. The serum levels of miR-21, miR-25, miR-146a, and miR-181a in patients with T1D (n = 29), LADA (n = 16), and T2D (n = 31) and in nondiabetic individuals (n = 19) were determined by quantitative real-time polymerase chain reaction, and receiver-operating characteristic (ROC) curves were evaluated to determine the discriminatory performances of these four miRNAs. Furthermore, target genes and pathways potentially modulated by these four miRNAs were predicted by bioinformatics analysis to investigate the possible functions of these miRNAs in autoimmune diabetes. Subsequently, multiple logistic regression analysis was performed to identify independent predictors for autoimmune diabetes, and a nomogram was established. Results. miR-21, miR-25, miR-146a, and miR-181a were significantly downregulated in the serum of patients with autoimmune diabetes compared with those in T2D patients and nondiabetic individuals (p<0.001). The areas under the ROC curves of these four miRNAs were greater than 0.80 (p<0.001). Bioinformatics analysis suggested that miR-21, miR-25, miR-146a, and miR-181a regulated multiple genes in pathways associated with immunity, inflammatory responses, hyperglycemia, and metabolism, which are involved in the pathogenesis of autoimmune diabetes. Multiple logistic regression analysis identified miR-25 (odds ratio (OR): 0.001, p<0.05), miR-146a (OR: 0.136, p<0.05), and fasting C-peptide levels (OR: 0.064, p<0.05) as independent predictors of autoimmune diabetes. Conclusions. miR-25 and miR-146a may serve as potential circulating biomarkers and provide insights into the pathogenesis of autoimmune diabetes.